مدلول " ليْس بشيء " عند الإمام النسائي - Ahmed Eid Ahmed Alitfy (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
In this study, I dealt with the term “nothing” according to Imam al-Nasa’i, collected and studied, and I followed the inductive, critical, and analytical approach, by identifying the narrators whom Imam al-Nasa’i said, “Nothing,” and comparing his words with those of critics and analyzing them, and then came to a ruling  It is clear in it after the critical study of each narrator, who numbered twelve narrators, in order to remove the confusion that occurred in the understanding of what is meant by it, and it was exposed, in it, to a brief translation of the imam, and showed the meaning of this term, through the interpretation of the imams after him, with comparison with the words of critics in  The narrator, and it was found that al-Nasa’i - may God have mercy on him - was one of the hard-liners in al-jarh and al-ta’deel.  The research concluded with the most important results, including: that Imam al-Nasa’i - may God Almighty have mercy on him - is considered one of the hard-liners in the wound and the modification, and that the narrator when it is proven that he is seized before his speech, and he is not harmed by what he erred in as long as he is not obscene in it, and he has the favor of the imams, and God knows best.